Differentiation and Functionality of Bone Marrow-Derived Mast Cells Depend on Varying Physiologic Oxygen Conditions - Möllerherm, Helene; Meier, Karsten; Schmies, Kathrin; Fuhrmann, Herbert; Naim, Hassan Y.; von Köckritz-Blickwede, Maren; Branitzki-Heinemann, Katja (Frontiers in Immunology, 2017)
Mast cells are long-living multifunctional innate immune cells that originate from hematopoietic precursors and specifically differentiate in the destination tissue e.g. skin, respiratory mucosa, intestine, where they mediate immune cell recruitment and antimicrobial defense. In vivo these tissues have characteristic physiological oxygen levels that are considerably lower than the atmospheric oxygen conditions (159 mmHg, 21% O2; 5% CO2) traditionally used to differentiate mast cells and to study their functionality in vitro. Only little is known about the impact of physiological oxygen conditions on the differentiation process of mast cells. This study aimed to characterize the differentiation of immature murine bone marrow-derived mast cells under physioxia in vitro (7% O2; 53 mmHg; 5% CO2). Bone marrow-derived suspension cells were differentiated in the presence of interleukin-3 with continuous, non-invasive determination of the oxygen level using a Fibox4-PSt3 measurement system without technique-caused oxygen consumption. Trypan blue staining confirmed cellular viability during the specified period. Interestingly, mast cells cultivated at 7% O2 showed a significantly delayed differentiation rate defined by CD117-positive cells, analyzed by flow cytometry and reached > 95% CD117 positive population at day 32 after isolation. Importantly, mast cells differentiated under physioxia displayed a decreased transcript expression level of hif-1α and selected target genes vegf, il-6, and tnf-α, but an increase of foxo3 and vhl expression compared to mast cells cultivated under normoxia. Moreover, the production of reactive oxygen species as well as the amount of intracellular stored histamine was significantly lower in mast cells differentiated under low oxygen levels which might have consequences for their function such as immunomodulation of other immune cells. These results show for the first time that physioxia substantially affect maturation and the properties of mast cells and highlight the need to study their function under physiologically relevant oxygen conditions.